Digital Food Consumption Behavior: The Role of Social Media, Self-Control, and Hedonic Motivation on Impulsive Buying in GoFood (Quantitative Study with Multiple Linear Regression Analysis) - Azlan Azhari (Mabny: Journal of Sharia Management and Business, 2026)
Purpose– This study aims to analyze the influence of Social Media, Self-Control, and Hedonic Shopping Motivation on Impulsive Buying in food purchases on GoFood in Makassar City. Methodology– This study used a quantitative approach with multiple linear regression analysis. The sample consisted of 100 respondents who were active GoFood users and were selected using accidental sampling. Data were collected through an online questionnaire with a 5-point Likert scale and analyzed using SPSS version 25. Findings– The results of the study show that simultaneously, Social Media, Self-Control, and Hedonic Shopping Motivation have a significant influence on Impulsive Buying in food purchases on GoFood. Partially, Social Media and Hedonic Shopping Motivation have a positive and significant influence on Impulsive Buying, while Self-Control has a negative and significant influence on Impulsive Buying. Hedonic Shopping Motivation is the most dominant variable in influencing the impulsive buying behavior of GoFood consumers. Implications– The implications of this research emphasize the importance of responsible digital marketing strategies through social media and the need to increase consumer self-control when using food delivery services. Furthermore, the GoFood platform is expected to develop spending management features and digital financial literacy education to help consumers control impulsive buying behavior. Originality– The originality of this research lies in the simultaneous integration of Social Media, Self-Control, and Hedonic Shopping Motivation variables in explaining Impulsive Buying in the context of online food delivery services, especially GoFood users in Indonesia.